Empowering Psychosomatic Medicine Practice Through Shared Decision-making - Yiming GOU; Zhimin FANG (Yixue yu zhexue, 2025)
Shared decision-making (SDM) centers on the "person with the illness" as the subject of clinical decisions, upholds "informed consent" as its guiding principle, and adopts "high-quality joint participation" as its clinical practice method. This aligns well with the holistic approach of psychosomatic medicine, which emphasizes the integration of physiological, psychological, and social information in patient care. Empowering psychosomatic medicine through SDM can deepen patients' understanding of mind-body interaction therapies, boost their confidence in overcoming illness, and ultimately support their journey from psychological well-being to physical health. However, practical challenges in implementing SDM continue to hinder the development of psychosomatic medicine. To address these issues, it is essential to adopt a multi-stakeholder collaborative approach that focuses on physician-led guidance in decision-making, effective patient participation, and institutional support for SDM mechanisms within hospitals. These efforts can help optimize SDM and enhance the practice of psychosomatic medicine.